Analisis Peranan Dan Tugas Staff Komisi C Dalam Mendukung Kinerja Dewan Komisi C DPRD Provinsi Sumatera Utara - Friska Fauziah Umardhi; Muhammad Ikhsan Harahap (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Every student at the university must complete an internship, especially at the Islamic State University of North Sumatra. Every student must have practical work experience to be able to start working after college. Internships are a good way to align theoretical knowledge with the real world of work because basically the theoretic knowledge learned in the classroom is not necessarily the same as what is done in the field. Working practices provide a great opportunity for students to interact directly with the world of business or work. Problems can arise from the failure to strike a balance between something intended and a situation that corresponds to the facts, which leads to the question